Surgical treatment of myasthenia gravis: 10 years of single center experience - Moraes Neto, José De Sá; Fonini, Jaqueline Schaparini; De Assis Cavalcanti Neto, Francisco; De Oliveira, Fernanda Aquino; Aranha, Gabriel Lunardi; Zambon, Antonio Alberto; Estephan, Eduardo De Paula; Zanoteli, Edmar; Pêgo-Fernandes, Paulo Manuel; Mariani, Alessandro Wasum (Frontiers in Neurology, 2025)
ObjectiveTo evaluate a 10-year experience in the surgical treatment of patients with myasthenia gravis, focusing on clinical and pharmacological outcomes.MethodsA retrospective single-center study was conducted based on prospective data collection from the Redcap® maintained by the Thoracic Surgery Department in a Brazilian tertiary hospital. Patients with myasthenia gravis (AchR positive), who underwent surgical treatment as an adjuvant to clinical therapy were included.ResultsThe study comprised 85 patients with a mean age of 43 years; 75% were female. Regarding the type of surgery, 24.7% underwent sternotomy and 75.3% minimally invasive approach. The median hospital stay was 4.0 days (p25 = 3.0; p75 = 5.5), and the median ICU stay was 1.0 days (p25 = 0.40, p75 = 2). Postoperative outcomes showed a corticosteroid reduction in 52 participants (61%), and 30 (35%) showed anticholinesterase reduction. The median dose of corticosteroids before surgery was 40.00 mg, and after surgery, 20.00 (p-value < 0.001). Based on Osserman classification, before surgery, it was observed that 4% had grade I, 15% grade IIa, 32% grade IIb, 31% grade III, and 18% grade IV. After surgery, it was observed that 28.5% were asymptomatic, 28% had grade I, 34% had grade IIa, 3.6% had grade IIb, and 5.9% had grade III. There was no statistical difference in clinical and pharmacological response in the analysis with and without thymoma and myasthenia (p-value 0.403; p-value 0.104). About the surgical approach, patients undergoing thymectomy by sternotomy have longer hospital and ICU stays with statistical significance (p-value <0.001; p-value 0.005).ConclusionThis study demonstrated that surgical treatment for myasthenia gravis is safe and effective for symptom control and medication reduction, regardless of the surgical approach, with shorter ICU and hospital stays through the minimally invasive approach.